HPV infection and endometriosis: a systematic review and meta-analysis - Oliveira, Geilson Gomes de; Eleutério Júnior, José; Eleutério, Renata Mírian Nunes (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Recent research has focused on the role of persistent ascending bacterial infections and sexually transmitted infections (STI) as a factor associated to endometriosis. Indeed, some studies investigated the possible role of HPV in endometriosis, but this topic remains inconclusive. Objective: The present study aims to meta-analyze research that assessed the presence of HPV infection in patients with endometriosis. Methods: MEDLINE, Embase, Scopus, LILACS, Cochrane Library, and OpenGrey were searched until February 10th, 2020. Search terms included “endometriosis” and “HPV” without language restrictions. The combined relative risks and 95% confidence interval (95%CI) were calculated, and heterogeneity was assessed with I-square (I2). Results: Meta-analysis with low heterogeneity found a relative risk of twice as much in women exposed to HPV in relation to the unexposed control. Conclusion: Results indicate that HPV could be a risk factor for developing endometriosis.